Distributed Parameter Estimation in Probabilistic Graphical Models - Mizrahi, Y; Denil, M; de Freitas, N (University of Oxford, 2014)
This paper presents foundational theoretical results on distributed parameter estimation for undirected probabilistic graphical models. It introduces a general condition on composite likelihood decompositions of these models which guarantees the global consistency of distributed estimators, provided the local estimators are consistent.